STUDENTS’ MOTIVATION AND RESPONSIVE PEDAGOGY IN LANGUAGE CLASSROOM - Syarifah Dahliana (Universitas Islam Negeri Banda Aceh, 2019)
Students’ motivation contributes to the successful teaching learning process as it determines self-engagement and participations in the classroom. Encouraging students’ motivation, then, becomes important for the teacher to achieve the teaching goal and to provide a meaningful learning process for the students. This research is aimed to discuss responsive pedagogy in encouraging students’ motivation to learn and participate in classroom learning process. One English speaking class becomes the object of the observation. The interviews with the teacher and some students were also part of data collection in order to obtain information about the students’ motivation in learning English speaking, teacher’s teaching strategy, and classroom interactions. The findings indicate that classroom activities are crucial in motivating students’ responsive learning. In addition, the teacher’s competency in creating a conducive environment and leading an interactive communication are the ways of the teacher influence students’ motivation in learning process.